Thailand : rice bowl of Asia - Watson, Jane Werner, 1915- (Champaign, Ill.: Garrard Publising Company, 1966)
Four stories are interwoven with a discussion of history, geography, description of the people and their way of life in this Southeast Asian country of Thailand.
Keywords: Thailand